El viaje circular : Causas da Decadência dos Povos Peninsulares de Antero de Quental como apocalipsis secular - Ricardo Ledesma Alonso (Amnis)
This article examines the meta-historical scheme outlined by Portuguese poet and philosopher Antero de Quental in his lecture Causas da Decadência dos Povos Peninsulares nos Últimos Três Séculos (1871). I argue that the Anterian scheme of peninsular history, structured in stages of « prosperity » (Late Antiquity and Middle Ages), « decadence » (16th-19th centuries) and « regeneration » (future), can be understood as a romantic reinterpretation of the design, concepts and images of biblical history and prophecy. This study aims to contribute to the discussions about the theological presuppositions of modern historical consciousness.